A sign of affection. 2 - Dashiell, Christine, 1984-; Vanstiphout, Carl (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2021)
"After struggling with her feelings for Itsuomi, Yuki's chosen love, an intense heart-to-heart between the two, sitting against a laundromat window watching the falling snow, has begun to deepen their relationship. But there's still much more progress to be made, and Yuki finds the world Itsuomi inhabits intimidating... How can they keep communicating when Itsuomi drops in and out of Yuki's life?" -- Page [4] of cover.